Działania afirmatywne na Uniwersytecie Harvarda - Hejwosz, Daria (Kultura-Społeczeństwo-Edukacja, 2012)
Affirmative action was introduced to the American universities in the 1960s. The aim of this policy was to benefit the underrepresented groups, especially African Americans both in the higher education and the job market. The affirmative action was introduced to ensure equal opportunities as well as cultural diversity. The policy of Harvard University towards African Americans, Asian Americans and the other excluded groups was analyzed in this article. Moreover, the attempt to reconstruct the current debate about outcomes of the affirmative action was made. The article also tries to answer the following questions: did the affirmative action increase the number of the minority groups at Harvard University? Has the policy of equal opportunities eliminated inequalities or, on the contrary has it deepened them?